Functional hydrogel empowering 3D printing titanium alloys - Weimin Zhang; Jiaxin Zhang; He Liu; Yang Liu; Xiao Sheng; Sixing Zhou; Tiansen Pei; Chen Li; Jincheng Wang (Materials Today Bio)
Titanium alloys are widely used in the manufacture of orthopedic prosthesis given their excellent mechanical properties and biocompatibility. However, the primary drawbacks of traditional titanium alloy prosthesis are their much higher elastic modulus than cancellous bone and poor interfacial adhesion, which lead to poor osseointegration. 3D-printed porous titanium alloys can partly address these issues, but their bio-inertness still requires modifications to adapt to different physiological and pathological microenvironments. Hydrogels composed of three-dimensional networks of hydrophilic polymers can effectively simulate the extracellular matrix of natural bone and are capable of loading bioactive molecules such as proteins, peptides, growths factors, polysaccharides, or nucleotides for localized release within the human body, by directly participating in biological processes. Combining 3D-printed porous titanium alloys with hydrogels to construct a bioactive composite system that regulates cellular adhesion, proliferation, migration, and differentiation in the local microenvironment is of great significance for enhancing the bioactivity of the prosthesis surface. In this review, we focus on three aspects of the bioactive composite system: (Ⅰ) strategies for constructing bioactive interfaces with hydrogels, and (Ⅱ) how bioactive composite systems regulate the microenvironment under different physiological and pathological conditions to enhance the osteointegration and bone regeneration capability of prostheses. Considering the current research status in this field, innovations in orthopedic prosthesis can be achieved through material optimization, personalized customization, and the development of multifunctional composite systems. These advancements provide essential references for the clinical translation of osseointegration and bone regeneration in various physiological and pathological microenvironments.